Pengaruh Partisipasi Penyusunan Anggaran Pada Kinerja Aparat Pemerintah Dengan Komitmen Organisasi Sebagai Variabel Pemoderasi - Andriyani, Tri; Putri, I G. A. M. Asri Dwija (E-Jurnal Akuntansi, 2019)
The population in this study were officials who were authorized in budgeting, namely 37 OPDs in Badung Regency. This study amounted to 121 respondents. The data analysis technique of this research uses MRA. The variable budgeting participation has a positive effect on the performance of local government officials with the budgeting coefficient participation value (X1) of 0.342 with a significance level of 0.000 whose value is smaller than the real level of 0.05. Organizational commitment variable strengthens the influence of budgeting participation on the performance of local government officials, the interaction coefficient value of budgeting participation with organizational commitment (X1X2) is 0.281 with a significance level of 0.000. With a value of R ^ 2 of 0.766, which means that 76.6% of the variation in performance of local government officials is able to explain the variable budgeting participation, and with organizational commitment as a moderating variable. Keywords: Budgeting, performance of local government apparatus, regional apparatus organizations